A 16, 000-yr-long sedimentary sequence from Lakes Peters and Schrader (Neruokpuk Lakes), northeastern Brooks Range, Alaska. Issue 3 (November 2019) - Benson, Christopher W.; Kaufman, Darrell S.; McKay, Nicholas P.; Schiefer, Erik; Fortin, David
Abstract: Sediments that accumulate in high-latitude lakes serve as valuable environmental archives of changing conditions in a region currently undergoing rapid change. A previously unexplored sedimentary sequence reaching back 16, 000 years from Lakes Peters and Schrader (Neruokpuk Lakes) in the northeastern Brooks Range (69°N), Alaska, shows distinct changes in accumulation rates and biophysical properties including bulk density (BD), organic matter (OM) content, and grain-size distribution at five widely distributed core sites. The oldest sediments contain little OM and accumulated rapidly as glaciers retreated around 15 ka. OM peaked between 12 and 10 ka along with Northern Hemisphere summer insolation. BD increased and OM decreased until around 5 ka, possibly reflecting a decrease in river-transported terrestrial OM. From 5–2 ka, OM consistently increased, suggesting a rise in river discharge, or a rise in summer temperatures, which led to higher productivity, or both. After 2 ka, sediments increased in BD and decreased in OM, suggesting glacier growth. Evidence for glacier expansion late during the Little Ice Age is weak, but increased sedimentation rates may reflect glacier retreat during the last century. This study provides a framework for future paleoenvironmental research of a rare archive in a relatively pristine Arctic setting.